1988
DOI: 10.1113/jphysiol.1988.sp017198
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spontaneous firing patterns of rat hippocampal neurones induced by volatile anaesthetics.

Abstract: SUMMARY1. The effects of the volatile anaesthetics, halothane, isoflurane and enflurane, on rat hippocampal CAI and CA3 neurones in in vitro preparations were studied by intracellular recording methods.2. The three anaesthetics, at concentrations similar to those used clinically (02-1-2 mM), initially increased and then subsequently decreased the spontaneous firing of CAI neurones without affecting the resting membrane properties or the EPSPs evoked by focal stimuli.3. The anaesthetics at these concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…This hypothesis is consistent with a previous study that reported that the bradycardiac agent and blocker of I h ZD 7288 augments the PTH and enhances the activity‐dependent slowing of conduction of CAPs C fibers 41. This idea is in agreement with the concept that a putative mechanism for drug‐mediated antinociception would involve hyperpolarization 13, 22…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis is consistent with a previous study that reported that the bradycardiac agent and blocker of I h ZD 7288 augments the PTH and enhances the activity‐dependent slowing of conduction of CAPs C fibers 41. This idea is in agreement with the concept that a putative mechanism for drug‐mediated antinociception would involve hyperpolarization 13, 22…”
Section: Discussionsupporting
confidence: 93%
“…It may be due to a transient increase in neuronal excitability as has been seen in the hippocampus in vitro 9. Also, it may reflect a preferential anesthetic depression of feed forward inhibition 52, leading to a larger response and/or more units being able to respond.…”
Section: Discussionmentioning
confidence: 93%
“…The channel-gating properties were very similar among all of the channels that we have tested (except Na v 1.8), and isoflurane at 1 MAC inhibited the peak amplitude of the currents mediated by Na v 1.2, Na v 1.4, and Na v 1.6 to around 30%. Others report that isoflurane suppresses firing frequencies of rat hippocampal neurons at clinically relevant concentrations (Yoshimura et al, 1985;Fujiwara et al, 1988). Moreover, recent studies showed that 30 M lidocaine reduced firing frequency to 21 Hz from a control frequency of 35 Hz in Fig.…”
Section: Discussionmentioning
confidence: 99%